2022
DOI: 10.1016/j.isci.2021.103549
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models for non-alcoholic fatty liver disease: Emerging platforms and their applications

Abstract: Summary Non-alcoholic fatty liver disease (NAFLD) represents a global healthcare challenge, affecting 1 in 4 adults, and death rates are predicted to rise inexorably. The progressive form of NAFLD, non-alcoholic steatohepatitis (NASH), can lead to fibrosis, cirrhosis, and hepatocellular carcinoma. However, no medical treatments are licensed for NAFLD-NASH. Identifying efficacious therapies has been hindered by the complexity of disease pathogenesis, a paucity of predictive preclinical models and ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 189 publications
0
64
0
Order By: Relevance
“…In the past years, numerous in vitro models of the liver have been proposed, not only for fundamental research but also to support pharmaceutical development with reliable high-throughput platforms. , In this context, two-dimensional models of the liver, intended as monolayers of hepatic cells grown on flat substrates such as Petri dishes or multiwell plates, were the first platforms exploited to evaluate the hepatotoxic response to the administration of active pharmaceutical ingredients in vitro. These types of models, which can rely both on primary cells and cell lines, thus providing robust and reproducible results, led the way for the production of more complex models. , Up to now, some recent models have been based on three-dimensional cultures, where the cells are cultured within matrices mimicking the hepatic extracellular environment . These platforms allow not only to reproduce the in vivo-like spatial organization of cells but also the interactions occurring between cells and the extracellular environment. , Moreover, culturing cells within a tridimensional construct provides them with a set of chemical and mechanical stimuli, similar to those experienced in vivo, which significantly enhances cell proliferation while mitigating the dedifferentiation phenomenon observable when culturing cell monolayers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past years, numerous in vitro models of the liver have been proposed, not only for fundamental research but also to support pharmaceutical development with reliable high-throughput platforms. , In this context, two-dimensional models of the liver, intended as monolayers of hepatic cells grown on flat substrates such as Petri dishes or multiwell plates, were the first platforms exploited to evaluate the hepatotoxic response to the administration of active pharmaceutical ingredients in vitro. These types of models, which can rely both on primary cells and cell lines, thus providing robust and reproducible results, led the way for the production of more complex models. , Up to now, some recent models have been based on three-dimensional cultures, where the cells are cultured within matrices mimicking the hepatic extracellular environment . These platforms allow not only to reproduce the in vivo-like spatial organization of cells but also the interactions occurring between cells and the extracellular environment. , Moreover, culturing cells within a tridimensional construct provides them with a set of chemical and mechanical stimuli, similar to those experienced in vivo, which significantly enhances cell proliferation while mitigating the dedifferentiation phenomenon observable when culturing cell monolayers …”
Section: Introductionmentioning
confidence: 99%
“…These types of models, which can rely both on primary cells and cell lines, thus providing robust and reproducible results, led the way for the production of more complex models. 6 , 7 Up to now, some recent models have been based on three-dimensional cultures, where the cells are cultured within matrices mimicking the hepatic extracellular environment. 8 These platforms allow not only to reproduce the in vivo-like spatial organization of cells but also the interactions occurring between cells and the extracellular environment.…”
Section: Introductionmentioning
confidence: 99%
“…HepG2 cells are widely used in in vitro NAFLD models because they have the characteristics of hepatocytes that accumulates intracellular lipids by FFA treatments such as oleic acid and/or palmitic acid [ 9 , 34 , 35 ]. Many studies have reported that the exposure of HepG2 cells to 0.5–1 mM of FFA for 24 h results in significant lipid accumulation [ 16 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The level of hepatic lipidosis was similar between Tlcd1/2 DKO and controls in the WD NASH mouse model, suggesting that TLCD1/2 can modulate NASH progression independently of hepatic DNL gene transcription and subsequent lipid accumulation. As mouse primary hepatocytes from Tlcd1/2 DKO and control mice responded similarly to a PA + LPS in vitro challenge, it suggests that a more physiological cell culture system, such as hepatocyte organoids, macrophage or stellate cell co-culture models 40 , may be required to understand the pathological mechanisms of TLCD1/2.…”
Section: Discussionmentioning
confidence: 99%